Strategi Manajemen Dalam Pengembangan Bisnis Pondok Pesantren Terhadap Aspek Sosial-Ekonomi - Alannawa, Sonia Rosta (Al Rikaz: Jurnal Ekonomi Syariah, 2024)
This study aims to analyze management strategies in the development of Islamic boarding school business by paying attention to its socio-economic aspects. The research method used is descriptive qualitative. The results of the discussion show that in developing the boarding school business, management strategies involving transformational leadership, entrepreneurship, and human resource development are the keys to socio-economic success. Transformational leadership is able to inspire and motivate organizational members, while the promotion of entrepreneurship not only creates economic growth but also supports the social development of the community. Human resource development, both in academic aspects and community empowerment, contributes positively to social and economic well-being. Through these measures, the boarding school can not only manage its business efficiently but also empower the community through education and economic initiatives, making the boarding school relevant and positively impacting society in the Modern Era. This research underscores the importance of practical steps in optimizing the positive impact on the socio-economic aspects of Islamic boarding schools, which are implemented through well-planned management strategies.